The Year in C-SPAN Archives Research : Volume 4 - Browning, Robert X., 1950- (C-SPAN Archives series., 2018)
The Year in C-SPAN Archives Research--Volume 4, edited by Robert X. Browning, advances our understanding of the framing of mental health, HIV/AIDS, policing, and public health, and explores subjects such as audience reactions in C-SPAN covered debates, the Twitter presidency of Donald Trump, and collaborative learning using the C-SPAN Video Library.